Best Practices of Pharmaceutical Services at the Primary Health Center in Samarinda City-East Kalimantan Province - Wardani, Hanie Kusuma (Journal for Quality in Public Health, 2024)
Primary health centers are government-owned first-level health care facilities that play a role in promotive and preventive through individual and public health efforts in their working areas. One type of service at a health center is pharmaceutical services. Pharmaceutical services at primary health centers have two functions, there are drug management and clinical pharmacy services. Pharmaceutical services at primary health centers are carried out in the Pharmacy Room led by a pharmacist. In carrying out both functions, pharmacists at primary health centers refer to the standards of pharmaceutical services at primary health centers as stated in the Regulation of the Minister of Health of the Republic of Indonesia Number 74 of 2016. This study aims to determine the implementation of pharmaceutical services at primary health centers in Samarinda City-East Kalimantan. The research method is descriptive method with quantitative approach. The population of this study were 26 pharmacists of primary health centers in Samarinda City. This study used saturated samples, meaning that all populations were sampled in this study. The data obtained were analyzed and presented descriptively. The results showed that the majority of primary health centers (92%) were non-inpatient health centers, had one pharmacist (85%) and two pharmacy vocational staff (46%). The average number of outpatients served was less than 50 per day (54%). All primary health centers pharmacists have conducted drug management except for the monitoring and evaluation stage of management. Meanwhile, clinical pharmacy activities have been carried out except for monitoring and reporting drug side effects.